Enzyme activities of agarwood (Aquilaria malaccensis Lamk.) stem under pathogenesis - R Samanta, P Tamuli, P Baruah, (Journal of Spices and Aromatic Crops, 2008)
Cellulase, pectinase, peroxidase and polyphenol oxidase activities were determined in healthy,naturally infected and inoculated agarwood (Aquilaria malaccensis) plant parts at varioustime intervals to study the changes in activities of these enzymes during pathogenesis. Samplesinfected naturally with Chaetomium globosum and Fusarium oxysporum exhibited higheractivity of all the enzymes compared to healthy samples